Examining membership and trading patterns in the Europian union - Buenafe, Cyrus Paolo M. (The Loyola Schools Review Social Sciences, 2009)
Gravity models have been used to understand the behavior of trade flows by various communities based on some geopolitical arrangement. Applying an augmented gravity model, the objectives of the paper are (1) to validate the relevance of the gravity model in explaining trade flow behavior among Europian states and (2) the highlight the relevance of the Europian Union in such behavior. He results validates result of earlier application of similar gravity models. In this study, results indicates that trade decreases by more than 50% as the distance of the trading counties are farther away. However, the results also show that trade decreases by roughly 20% if trade is done between EU member-states. Political and psychological factors such as apprehension of Easterns Europian Counties to trade with Western Europe after fall of communism in the 1990 and the unbalanced development of the Western Europe vis-a-vis Eastern Europe can be cited as possible reasons for the stunting of grade growth among EU member-states. Such implications are very critical if and when other similar regional associations such as ASEAN consider improving its trading relationships.